Meretas Involusi Kajian Hukum Islam di Indonesia: Pengalaman Fakultas Syariah dan Hukum UIN Sunan Kalijaga Yogyakarta - Hasan, Noorhaidi (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
The study of Islamic law requires a shifting paradigm from text to context and demands an inter-disciplinary approach involving  various  disciplines  in  social  sciences.  A  text-based legal-normative  approach  is  no  longer  adequate  to  ensure  the relevance of the study of Islamic law with the current changes as a  result  of  modernization  and  globalization.  Perspectives  of social sciences provides not only the lens to see Islamic law as a fact  social,  but  also  offers  the  analitical  frameworks  to  explain how  Islamic  law  engages  with  the  context  and  receives  new meanings  and  interpretations  in  its  complex  interaction  with other forms of social practices.  In  tandem  with  growing awareness  among  Muslim  intellectuals  of  the  importance  of actualizing Islamic law with the spirit of changes, the studies and researches  at  the  Faculty  of  Sharia  and  Law  at  Sunan  Kalijaga State Islamic University of Yogyakarta have thrived by utilizing and integrating social sciences into their paradigm, method and analytical  construct.  Within  this  context  the  so-called  "mazhab Yogya?  came  into  being.  This  new  trend  of  thought  pays  a special attention to the effort of reactualizing  fiqh  as knowledge about  the  basic  principles  used  as  a  reference  in  formulating Islamic law in accordance with local context.